2020
DOI: 10.1530/jme-19-0207
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial stress protein HSP60 regulates ER stress-induced hepatic lipogenesis

Abstract: Endoplasmic reticulum (ER) stress and mitochondrial dysfunction are associated with hepatic steatosis and insulin resistance. Molecular mechanisms underlying ER stress and/or mitochondrial dysfunction that cause metabolic disorders and hepatic steatosis remain to be fully understood. Here, we found that a high fat diet (HFD) or chemically induced ER stress can stimulate mitochondrial stress protein HSP60 expression, impair mitochondrial respiration, and decrease mitochondrial membrane potential in mouse hepato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…Specifically, HSP60 showed to upregulate proliferator-activated receptor gamma coactivator 1 α1 expression, a chief regulator in mitochondrial biogenesis process [51,52]. Furthermore, ER UPR has been suggested to activate mitochondrial UPR [53,54]. These findings are in agreement with our study that showed tunicamycin-associated increases in mitochondrial mass, as well as in the expression of HSP60 and HSPA9 mitochondrial UPR mediators, with HSPA9 being completely inhibited by EUK-134.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, HSP60 showed to upregulate proliferator-activated receptor gamma coactivator 1 α1 expression, a chief regulator in mitochondrial biogenesis process [51,52]. Furthermore, ER UPR has been suggested to activate mitochondrial UPR [53,54]. These findings are in agreement with our study that showed tunicamycin-associated increases in mitochondrial mass, as well as in the expression of HSP60 and HSPA9 mitochondrial UPR mediators, with HSPA9 being completely inhibited by EUK-134.…”
Section: Discussionsupporting
confidence: 92%
“…De novo lipogenesis occurs in ER and is regulated by membrane proteins sterol regulatory element-binding proteins (SREPB1c and SREPB2, for fatty acids and cholesterol respectively) and related pathways [24,25,38,46]. In presence of insulin resistance, these proteins are upregulated, leading to increased lipogenesis and further lipotoxicity [24,25,28,38,50]. Moreover, the hepatic accumulation of fat can lead to altered composition of ER membrane, leading to impaired functionality [46,51,52].…”
Section: Endoplasmic Reticulum Stress and Mitochondrial Dysfunction In Nafldmentioning
confidence: 99%
“…An important feature of NAFLD and its progression to NASH is mitochondrial stress [ 14 ]. To determine whether the reduction in hepatic steatosis and increase in mitochondrial mass induced by NCT translated to reduced mitochondrial stress, we examined the expression of HSP60, a mitochondrial chaperone that is induced by mitochondrial stress, including HFD [ 15 ] (Fig. 3M ).…”
Section: Resultsmentioning
confidence: 99%